Zakon karmelitów w Kożuchowie = The Carmelite order in Kożuchów - Podolan, Eligiusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article entitled "TheCannelite order in Kożuchów" I tried to include a few observations concerning the presence of the convent in the city. The remains o f the Carmelite order are a valuableproof of its existence and of its activity in the fast developing Kożuchów of the modern age.
Keywords: Kożuchów - historia; Karmelici (zakon)